Three-dimensional printing in congenital heart disease: Considerations on training and clinical implementation from a teaching session. Issue 10 (October 2019) - Biglino, Giovanni; Milano, Elena G; Capelli, Claudio; Wray, Jo; Shearn, Andrew IU; Caputo, Massimo; Bucciarelli-Ducci, Chiara; Taylor, Andrew M; Schievano, Silvia
In light of growing interest for three-dimensional printing technology in the cardiovascular community, this study focused on exploring the possibilities of providing training for cardiovascular three-dimensional printing in the context of a relevant international congress and providing considerations on the delivery of such courses. As a second objective, the study sought to capture preferences in relation to three-dimensional printing uses and set-ups from those attending the training session. A survey was administered to n = 30 professionals involved or interested in three-dimensional printing cardiovascular models following a specialised teaching session. Survey results suggest the potential for split training sessions, with a broader introduction for those with no prior experience in three-dimensional printing followed by a more in-depth and hands-on session. All participants agreed on the potential of the technology in all its applications, particularly for aiding decision-making around complex surgical or interventional cases. When exploring setting up an in-house three-dimensional printing service, the majority of participants reported that their centre was already equipped with an in-house facility or expressed a desire that such a facility should be available, with a minority preferring consigning models to an external third party for printing.